Sulfur-Deficient Transfer Ribonucleic Acid in a Cysteine-Requiring, “Relaxed” Mutant of Escherichia coli - Harris, Charles L. (1969)
A cysteine-requiring mutant of the parent strain Escherichia coli Hfr Cavalli (RC(rel), Met(−), λ) has been isolated. The mutant was selected by using replica plating after mutagenesis by N-methyl-N′-nitro-N-nitrosoguanidine. The mutation appears to be in the gene for sulfite reductase, since the mutant could utilize sulfide but not sulfite as a sulfur source. The mutant was found to be RC(rel) with respect to both methionine and cysteine. During cysteine starvation, transfer ribonucleic acid (tRNA) deficient in 4-thiouracil was produced, and in vivo studies indicate that this tRNA can accept sulfur groups to a greater extent than normal tRNA. Further, there were differences both in the rate and extent of amino acid acceptance between normal and sulfur-deficient tRNA. This suggests that thionucleotides are involved in at least one of the biological functions of the tRNA molecule.